Exploring the therapeutic potential of fucoidans and sodium alginates from South African brown seaweeds - Daub, Chantal Désirée (Rhodes University, 2026)
The increasing prevalence of type 2 diabetes and cancer poses significant global health challenges, prompting the need for novel treatment strategies due to the shortcomings of current approaches. Exploring natural bioproducts, particularly those sourced from marine environments, has emerged as a promising route. Among these compounds, polysaccharides such as fucoidan and sodium alginate, found abundantly in brown seaweeds, have demonstrated intriguing anti-diabetic and anti-cancer properties. However, despite previous studies highlighting their bioactivities, the underlying mechanisms remain poorly understood. In addition, South African brown seaweeds, have not been thoroughly explored for their potential. Therefore, the aim of this study was to screen fucoidans and sodium alginates from South African seaweeds to investigate their bioactivity against enzymatic targets relevant to type 2 diabetes mellitus (T2DM) and assess their effects on various cellular processes pertinent to anti-cancer activity, whilst also attempting to gain further insights into the mechanism of their bioactivities. Fucoidans and sodium alginates used in this study were successfully extracted from four brown seaweed species, namely Ecklonia maxima, Ecklonia radiata, Sargassum elegans, and Sargassum cymosum, sourced from the South African shoreline. Chemical composition and structural features were comprehensively assessed using HPLC, FTIR, NMR, TGA, and XRD spectroscopy. The results showed that fucoidans from Ecklonia species were predominantly composed of monosaccharides, with glucose as the primary component, while those from Sargassum species contained higher sulphate levels and lower carbohydrate contents, consisting mainly of L-fucose. Sodium alginates were characterised by a higher content of mannuronic acid than guluronic acid. Structural elucidation provided further information on the presence of key structural features in both fucoidans and sodium alginates. Analysis of the anti-diabetic potential of fucoidan and sodium alginate extracts was done by evaluating their inhibitory effects on the key carbohydrate-degrading enzymes relevant to Type 2 diabetes treatment: α-amylase, α-glucosidase, sucrase, and maltase. The results showed significant enzyme inhibition by fucoidans extracted from E. maxima, E. radiata, and S. elegans. Importantly, fucoidans from E. radiata and S. elegans demonstrated potent inhibition of α-glucosidase, maltase, and sucrase, surpassing the efficacy of the commercial anti-diabetic drug acarbose. In contrast, E. maxima fucoidan could only compete with acarbose’s efficacy when inhibiting α-glucosidase. A very significant finding of the study was that none of the fucoidans exhibited inhibitory effects on α-amylase. Furthermore, insights into the inhibition mechanism of α-glucosidase, maltase, and sucrase by the fucoidans were gained using linear and nonlinear regression methods. EnzymeML, a modern approach to enzyme kinetics analysis, identified the fucoidans from E. radiata and S. elegans as mixed-type inhibitors of α-glucosidase, exhibiting characteristics of both competitive and uncompetitive substrate inhibition along with evidence of enzyme inactivation. Traditional kinetic analysis revealed a mixed inhibition pattern of fucoidans from E. radiata and S. elegans for sucrase and maltase inhibition. The anti-cancer effects of the fucoidans and sodium alginates were also assessed in the HCT116 colon cancer cell line, using standard techniques such as cell viability, proliferation, adhesion, migration, spheroid formation, and colony formation assays. Human colon cancer cells were the most sensitive to the treatment with E. maxima and S. cymosum fucoidan, which inhibited crucial metastasis-related processes such as cell adhesion, cell migration, spheroid formation, and anchorage-independent colony growth. Although a single underlying mechanism could not be pinpointed, these effects appear to be driven by changes in key interconnected signalling pathways, such as Wnt/β-catenin, AKT, FAK, and the Hippo pathway. Together, these changes in cellular functions and signalling pathways indicate a multifaceted impact on processes critical for metastatic progression. In summary, this study demonstrates promising anti-diabetic and anti-cancer activities for fucoidan extracts from South African seaweeds. Furthermore, this study also contributes to a deeper understanding of these activities by offering insights into their possible mechanisms of action.
insights into their anti-diabetic and anti-cancer properties and mechanisms
Keywords: Diabetes (http://id.loc.gov/authorities/subjects/sh85037456); Cancer (http://id.loc.gov/authorities/subjects/sh85019492); Fucoidan (https://www.wikidata.org/wiki/Q1144687); Sodium alginate (https://www.wikidata.org/wiki/Q1187513)